THE USE OF ENGLISH SPEECHES CHANNEL IN IMPROVING STUDENTS' LISTENING COMPREHENSION - Nur Aziza; Baso, Farisha Andi; AM, St. Asmayanti (English Language Teaching Methodology, 2024)
This research aimed to find out whether English speeches channel improve the students’ listening comprehension at eleven grade in SMAN 1 Gowa. This research used quantitative method in type of pre-experimental research. The data was collected through pre-test, treatment and post-test. The population were the students of SMAN 1 Gowa and the sample were the X MIPA 4 in SMAN 1 Gowa. The sampling technique used in this research was purposive sampling technique.The research findings showed that the students’ scoring achievement before and after using English Speeches Channel was significantly different. The students’ pre-test mean score in terms of accuracy (Answering properly and correctly) was 63, 33 to be 80, 00 in post-test with 26, 46% improvement. Then, the mean score in terms of listening in specific information was 64, 44 to be 80, 28 in post-test with 24, 58% improvement. The t-test analysis showed that Sig. (2-tailed) is 0.000 which is smaller than α = 0.05. It means that there was a significant difference of students listening comprehension before and after using English Speeches Channel. Based on the findings, it can be concluded that English Speeches Channel was effective to improve students’ listening comprehension at the ten Grade of SMAN 1 Gowa in the Academic Year 2022/2023.